Comparative Criteria Study of Dynamic Balancing in Pateints with Patello-Femoral Pain - Hamid Reza Mokhtari-Nia; Esmaeil Ebrahimi; Mahyar Salavati (Journal of Rehabilitation, 2005)
Objective: Reduced proprioception, Pain, changes in muscle activity patterns are sawn in PFPS. Balance is dependent on proprioception, visual, somatosensory and vestibular systems. So it is possible that balance be weaker in PFPS. The objectives of this study was the evaluation of the effect of patellofemoral pain on balance status of patients and comparing the balance between two groups.Anterior-Posterior, Medio-lateral and overall indexes were evaluated.